Increasing incidences and changes in treatment trends of clavicle fractures in adults during 2 decades in Denmark: a nationwide study on data from the Danish National Patient Registry - Ida Tryggedsson; Bjarke Viberg; Per Hviid Gundtoft; Ilija Ban; Søren Overgaard; Tazio Maleitzke; Arvind von Keudell (Acta Orthopaedica)
Background and purpose: Clavicle fractures are common shoulder injuries, but treatment strategies are debated. While a non-surgical approach has been preferred historically, recent studies suggest surgical intervention may reduce non-union rates and improve outcomes for displaced fractures. Despite ongoing research there is still no consensus on the optimal treatment choice. We aimed to report national incidences and trends in treatment of clavicle fractures in Denmark across 2 decades. Methods: The Danish National Patient Register was used to extract data on clavicle fracture diagnosis and treatment in patients aged 18 and above from 1996 to 2018. Primary treatment was categorized as surgical if a relevant surgical procedure code was registered within 3 weeks of the fracture code, otherwise treatment was defined as non-surgical. Results: There were 81,597 clavicle fractures recorded; 67% were in men and the mean age was 50.3 years (standard deviation [SD] 19.5). The overall fracture incidence was 82/100,000/person-years, increasing by 11% from 76 in 1996 to 84 in 2018. The incidence was more than 50% higher in males (113) than females (53). 6,096 cases (7.5%) were treated surgically, mainly with plate osteosynthesis (94%). The surgical rate increased from 1% in 1996 to 14% in 2011, whereafter it decreased again. In 2018, 7% of clavicle fractures were treated surgically, with inter-hospital variations ranging from 0 to 15%. Conclusion: The incidence of clavicle fractures increased over the period. Non-surgical treatment remained prevalent, though surgical rates fluctuated with plate osteosynthesis being the preferred method.